Causal relationship between atrial fibrillation/warfarin and cutaneous melanoma: a two-sample Mendelian randomization study - Xiaowu, Wang; Qiang, Zhou; Yike, Han; Wu, Zhixuan; Yiheng, Jin; Xuemei, Chen; Sen, Lin; Jiong, Chen (Frontiers in Medicine, 2024)
In recent years, the relationship between malignant tumors and atrial fibrillation has attracted more and more attention. Atrial fibrillation can also cause a series of adverse events, such as the risk of thromboembolism. Also, Warfarin is often used here. But, the relationship between cutaneous melanoma and atrial fibrillation, and between cutaneous melanoma and warfarin is still unclear. Therefore, we used a two-sample mendelian randomization to assess the causal relationship between atrial fibrillation/ warfarin and cutaneous melanoma (cM).Methods: Firstly, Atrial fibrillation (ukb-b-11550; nCase=3518, nControl=459415) and warfarin (ukb-b-13248; nCase=4623, nControl=458310) as exposures, with genome-wide association studies (GWAS) data from the UK Biobank. And cM (ieu-b-4969; nCase=3751, nControl=372016) as outcome, with GWAS data from the IEU Open GWAS project. Subsequently, single-nucleotide polymorphisms (SNPs) were filtered from GWAS studies using quality control measures. In addition, two-sample Mendelian randomization (MR) analysis was performed to explore the causal relationship between atrial fibrillation or warfarin and cM and used inverse variance weighting (IVW) as the primary analytical method. Finally, relevant heterogeneity and sensitivity analysis were performed to ensure the accuracy of the results.Results: A causal relationship between atrial fibrillation and cutaneous melanoma was observed, and between warfarin and cutaneous melanoma.The atrial fibrillation may play a causal role in the development of cutaneous melanoma, but the mechanism and the causal relationship between warfarin and cutaneous melanoma needs to be further elucidated.